Use of a Just-in-Time Teaching technique in an introductory acoustics class - Neilsen, Tracianne B.; Gee, Kent L. (2012)
The goal of active-learning techniques is to encourage the students to become involved with the material and take ownership for their learning, which fosters long-term knowledge and enjoyment of the subject. In this era of student-based learning outcomes, an active-learning approach is important because it focuses on what the students are doing to facilitate learning instead of what the instructor is trying to teach. To benefit most from class time, the students need to have the opportunity to actively engage with the material beforehand. If meaningful pre-class activities are required, it is easier to interact with the students during class. Some key methods for encouraging active learning during class include incorporating their pre-class experiences, conducting discussions, encouraging student participation, and evaluating student understanding with a response system, such as i-clickers. After the class time, students need apply what they have learned in answering additional questions on homework assignments and in hands-on laboratory experiences. Lessons learned after several years' worth of step-by-step efforts to approach these goals in an introductory acoustics class, which serves a wide range of majors as a general science elective, are presented.